The Sight Distance Planning for Road User Safety : A Case of Jalan Pasukan Sindangkasih-Majalengka - Nurhasanah, Rini; Rifai, Andri Irfan; Taufik, Mohamad; Sari, Yusra Aulia (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to provide practical and applicable solutions to improve road safety on the Troop-Sindangkasih Road section in Majalengka Regency, West Java, by analyzing road visibility using empirical data and the Bina Marga method. The primary data consisted of looking for a literature review on the classification of road classes based on their functions, calculation of visibility, while for secondary data collected about the location map of this study. The results show that visibility planning can be improved to improve traffic efficiency and reduce the risk of accidents. The research could also consider the influence of different vehicle types and weather conditions on visibility requirements to refine the standards set by the Geometric Planning Procedures for Intercity Roads. It is also hoped that this research will increase awareness of the importance of visibility planning for overall road safety to avoid accidents.